2021
DOI: 10.1101/2021.10.26.466023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extrinsic motivators drive children’s cooperation to conserve forests

Abstract: Forests are essential common-pool resources. Understanding school-aged children and adolescents’ motivations to conserve forests is critical for improving conservation education. In two experiments with school age children and adolescents (age range: 6-16; N=1088), we demonstrate that extrinsic, rather than intrinsic motivations lead to successful cooperation in common-pool goods games to maintain a forest. We investigate participants from three nationalities (China, D. R. Congo and U.S.) and find certainty of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…An attraction towards other humans is well established in the literature as a temperament trait, also known as sociability (Rettew, 2013). Bowie et al (2021) directly tested the AH against Wilson's biophilia hypothesis. In a cross-cultural study of 1088 children in Congo, China and the US, researchers found no evidence for an intrinsic motivation in children to save forests.…”
Section: Physiological and Neurological Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…An attraction towards other humans is well established in the literature as a temperament trait, also known as sociability (Rettew, 2013). Bowie et al (2021) directly tested the AH against Wilson's biophilia hypothesis. In a cross-cultural study of 1088 children in Congo, China and the US, researchers found no evidence for an intrinsic motivation in children to save forests.…”
Section: Physiological and Neurological Markersmentioning
confidence: 99%
“…We conclude that a revised hypothesis exploring biophilia is necessary, given the rise in the popularity of biophilia, which has consequences in several key areas. For example, conservation education assumes people are intrinsically motivated to maintain or increase biodiversity, when recent work has found that this Is not the case (Bowie et al, 2021). Urban planning is increasingly treating access to biophilic areas as a social justice issue, even though these areas might be harmful when treated with herbicides and pesticides (Chawla, 2015).…”
mentioning
confidence: 99%